Emotional intelligence and organizational culture as pillars of teaching practice (Revista Innova Educación, 2019)
The purpose of the research was to determine the correlation between emotional intelligence and the organizational culture of teachers at the Institución Educativa Secundaria Andrés Avalino Cáceres de Puno - Perú (2015). It was carried out from the quantitative approach, descriptive type, and cross-correlational design. The sample consisted of 22 teachers with a census sample. The technique for obtaining data was the survey and two pertinent questionnaires were applied as instruments to each variable. The presentation of the results was through frequency tables, reaching the conclusion that there is a significant and positive relationship between emotional intelligence and organizational culture.
Keywords: Leadership; motivation; educational organization; institutional climate